Pengaruh Media Kotak Huruf terhadap Kemampuan Keaksaraan Anak Usia 5-6 Tahun di PAUD Harapenta Namuseng T.A 2024 - Nola Sonia Berutu; Wan Nova Listia (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The problem in this study is the Influence of Letter Box Media on Literacy Skills of 5-6 Year Old Children at PAUD Harapenta Namuseng. This study aims to determine the influence of letter box media on literacy skills of 5-6 year old children. The method used in the study is a quantitative method, with a one group pretest-posttest design. The research sample was 10 children aged 5-6 years. The data collection technique used was observation. Using the Wilcoxon test, namely by comparing Tcount with Ttable N = 10 α = 0.05 Ttable = 8 where Tcount> Ttable (55> 8), which means the hypothesis is accepted. So it can be stated that there is an influence of the use of letter box media on literacy skills of 5-6 year old children at PAUD Harapenta Namuseng T.A 2024/2025.